2003
DOI: 10.1074/jbc.m304943200
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interaction of Target SNAREs with the Kv2.1 Channel

Abstract: Previously we suggested that interaction between voltage-gated K ؉ channels and protein components of the exocytotic machinery regulated transmitter release. This study concerns the interaction between the Kv2.1 channel, the prevalent delayed rectifier K ؉ channel in neuroendocrine and endocrine cells, and syntaxin 1A and SNAP-25. We recently showed in islet ␤-cells that the Kv2.1 K ؉ current is modulated by syntaxin 1A and SNAP-25. Here we demonstrate, using co-immunoprecipitation and immunocytochemistry anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 35 publications
2
20
1
Order By: Relevance
“…Previous work had shown that these t-SNAREs can bind to and regulate the gating of Kv2.1. [15][16][17][18] However, since the gating of the delayed rectifier does not change with apoptosis, 2 the neurotoxin results, in concert with our trafficking experiments, are most consistent with the requirement of t-SNARE proteins for the membrane fusion required for insertion of new channels into the cell surface. This conclusion also is in accordance with the observations that overexpression of syntaxin in cell lines inhibits exocytosis 19 and Kv2.1 surface expression.…”
Section: Discussionsupporting
confidence: 79%
“…Previous work had shown that these t-SNAREs can bind to and regulate the gating of Kv2.1. [15][16][17][18] However, since the gating of the delayed rectifier does not change with apoptosis, 2 the neurotoxin results, in concert with our trafficking experiments, are most consistent with the requirement of t-SNARE proteins for the membrane fusion required for insertion of new channels into the cell surface. This conclusion also is in accordance with the observations that overexpression of syntaxin in cell lines inhibits exocytosis 19 and Kv2.1 surface expression.…”
Section: Discussionsupporting
confidence: 79%
“…Both effects may require or be influenced by interactions of S1A with other SNARE proteins. For example, Michaelevski et al (25) report that Kv 2.1 channel activity is differentially regulated depending on whether S1A is expressed alone or in combination with its partner t-SNARE, SNAP-25, and similar data have been obtained for S1A and SNAP-23 interactions with CFTR (31). At present, we do not know whether SNAP-23 modifies the action of S1A on ENaC trafficking or gating.…”
Section: Fig 2 Enac Current Inhibition Is Composed Of Two Componentsmentioning
confidence: 57%
“…This interaction would provide a means to finely regulate vesicle membrane fusion and coordinate this process with Ca 2ϩ entry, which signals secretion (13). This so-called "excitosome" model has been extended to include other voltage-dependent channels of neuronal tissues such as Kv 2.1 (11,25). In addition, channels from non-excitable cells are regulated via interactions with SNARE proteins.…”
Section: Fig 2 Enac Current Inhibition Is Composed Of Two Componentsmentioning
confidence: 99%
“…This study provides the possibility that the SNARE complex may functionally modulate those transporters. Indeed, the properties of two ion channels, Kv2.1 potassium channel and cystic fibrosis transmembrane regulator chloride channel, are reported to be directly affected by the target SNARE complex (23,24), as mediated by their direct interaction with the H3 domain of syntaxin 1A (45,46). Moreover, accumulating evidence also reveals that syntaxin 1A interacts with other membrane proteins and regulates their functions, and its H3 domain is the only reported binding site (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies from the ion channels indicate that Kv2.1 potassium channel and cystic fibrosis transmembrane regulator chloride channel, which reside on the plasma membrane to control the intracellular or extracellular concentrations of respective ions, are functionally regulated by the t-SNARE complex (23,24). Because the t-SNARE complex acts on the ion channels, and syntaxin 1A physically interacts with and functionally regulates those neurotransmitter transporters, it is most likely that other SNARE proteins or the SNARE complex may modulate those transporters.…”
mentioning
confidence: 99%